PLURALISME HUKUM DALAM PERSPEKTIF ANTROPOLOGI - SURYATNI LUH (JURNAL MITRA MANAJEMEN, 2013)
ABSTRACTAccording to F. Von Benda-Bechmann, legal pluralism is a condition in which more thanone legal systems or institutions working side by side in legal activities that connect each otherin one community group. On the other side, the anthropology study regarding of law is givingattention to facets of human culture that are associated with the phenomenon of the law,especially in its function as a mean of social control. In regards of that, the theme ofAnthropological study gives more attentions to the phenomenon of legal pluralism which isfocused to the plural ways how to settle the problem through traditional mechanisms first,before takes a route to the dispute settlement institution. Therefore the legal pluralism inanthropological perspectives are cultural activities that serves its function as social controldevices in a society where law is studied as an integral part of the culture as a whole, insteadof a separate autonomous institutions in terms of other cultures. So to understand the place ofthe law in the structure of society, at first, it is a must to understand the socio-cultural life ofthe community holistically. It reaffirms that, law became one of the cultural products that cannot be separated in terms of human life in society, such as politics, economy, socialorganization, ideology and religion.Keywords: Legal Pluralism, Anthropology of Law, Cultural Activity, Social Control